Driving effects of spatiotemporal evolution of the water resources carrying capacity in the Yellow River Basin (Henan section) - Xiaoyan Wang; Wenhao Wang; Chuang Yan; Jinjuan Gao (Scientific Reports)
Abstract The water resources carrying capacity (WRCC) is a crucial indicator for assessing social, economic and ecological sustainability supported by water resources. While there are abundant studies on the WRCC, there remains a need to thoroughly analyze the driving effects of WRCC evolution. In this study, an index-based WRCC evaluation system was constructed, and a comprehensive evaluation model was employed to assess the spatiotemporal evolution of the WRCC in the Yellow River Basin (YRB) (Henan section). Then, the driving forces and factors of WRCC evolution were analyzed from a spatiotemporal perspective, thus clarifying the driving effects of WRCC differences. The results indicated that (1) the WRCC in the YRB (Henan section) exhibited a growth trend from 2010 to 2022, and the WRCC was significantly higher in upstream cities than that in downstream cities; (2) the core driving forces of WRCC evolution changed from economic and social progress to ecological and economic development; (3) the key driving factors influencing WRCC evolution were the per capita disposable income of urban residents, the urbanization rate and the gross domestic product (GDP) per capita. This study offers a novel research perspective to increase the WRCC and contributes to the formulation of targeted development measures.